Testing the climate variability hypothesis in thermal tolerance limits of tropical and temperate tadpoles. (1st February 2016) - Gutiérrez‐Pesquera, L. M.; Tejedo, M.; Olalla‐Tárraga, M. Á.; Duarte, H.; Nicieza, A.; Solé, M.
Abstract: Aim: The climate variability hypothesis (CVH) states that a positive relationship may exist between the breadth of thermal tolerance range and the level of climatic variability experienced by taxa with increasing latitude, especially in terrestrial ectotherms. Under CVH, we expected to find a correspondence between both thermal tolerance limits (CTmax and CTmin), ambient extreme temperature and the range sizes of species. We examined the validity of these predictions in a lowland tropical and a temperate tadpole assemblage. Location: Lowland Neotropics (Bahia, Brazil) and Palaearctic (Iberian Peninsula and North Africa). Method: We employed phylogenetic eigenvector regression (PVR) and Pagel's lambda to analyse phylogenetic signals in CTmax and CTmin. We used phylogenetic regression analyses (PGLS) to test the relationships between thermal limits, range size and temperature predictors (measured at the macroscale and microhabitat levels) and phy‐ANOVA to compare both the physiological traits and thermal regimen in both tropical and temperate assemblages. Results: We documented moderate‐to‐strong phylogenetic signal in both heat and cold tolerance. Temperate‐zone tadpoles had broader thermal tolerances than tropical ones. Thermal tolerance range was correlated with range sizes and was explained by seasonal thermal range predictors at the global scale. Both macro‐ and microclimate temperature variables provided the best predictive multivariate models of thermal limits at the global scale. Microclimatic predictors, however, were the main determinants of CTmax and CTmin variation at the local level of tropical and temperate communities respectively. Main conclusions: Thermal tolerance range increases with latitude in tadpoles due to the higher increase in cold tolerance in temperate tadpoles. At the global scale, both macro‐ and microenvironment thermal information were reliable predictors of critical thermal limits and thermal tolerance range, as CVH predicts. However, thermal limits were best predicted by temperatures of the micro‐habitat at the regional level, thus suggesting that physiological thermal boundaries may be governed by thermal selection.